2016
DOI: 10.1016/j.whi.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment and Gestational Weight Gain among U.S. Mothers

Abstract: Background Education is an important social determinant of many health outcomes, but the relationship between educational attainment and the amount of weight gained over the course of a woman's pregnancy (gestational weight gain (GWG)) has not been clearly established. Methods We used data from 1979-2010 for women in the National Longitudinal Survey of Youth 1979 cohort (n= 6344 pregnancies from 2769 women). We used generalized estimating equations to estimate the association between educational attainment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 62 publications
(76 reference statements)
4
16
0
Order By: Relevance
“…One prior study reported an increased risk of excessive gestational weight gain among African American and Latina women, although the results were not significant after adjusting for relevant covariates. The contradictory findings related to race/ethnicity may at least partially be explained by socioeconomic factors, which are also associated with gestational weight gain and often confounded with race/ethnicity …”
Section: Discussionsupporting
confidence: 90%
“…One prior study reported an increased risk of excessive gestational weight gain among African American and Latina women, although the results were not significant after adjusting for relevant covariates. The contradictory findings related to race/ethnicity may at least partially be explained by socioeconomic factors, which are also associated with gestational weight gain and often confounded with race/ethnicity …”
Section: Discussionsupporting
confidence: 90%
“…Consistent with other research findings, our results suggest several maternal characteristics, including maternal age, race/ethnicity, education, and income were associated with an increased risk for both inadequate and excessive gestational weight gain (Cohen et al, 2016; Samura et al, 2016). Associations between sociodemographic factors and GWG are complex, and further studies are needed to explore the multifaceted relationships between these factors.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the large number of publications regarding the association between socioeconomic status and GWG, the literature is inconsistent [ 32 , 33 , 39 41 , 68 , 69 ]. Women with low income have an increased risk for both excessive and inadequate GWG [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, a higher risk of gaining weight outside of the recommendations was found in women with a lower level of education [ 32 , 40 , 71 , 72 ]. Cohen et al suggested that higher education plays a role in healthier GWG for some, but not all, groups of pregnant women [ 33 ]. In most cases, higher education was associated with a lower chance of inadequate GWG.…”
Section: Discussionmentioning
confidence: 99%